(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research aim to identify the Availability Degree of Organizational Identification Dimensions of Kindergartens Care takers in Lattakia City, and to identify the difference in the degrees of the sample according to variables (educational qualification, experience, training courses). The sample of (198) Kindergarten care takers for the academic year 2018/2019. The present research used the descriptive analytical approach. To achieve the object of the research a questionnaire has been included (36) methods, distributed to three dimensions (similarity, loyalty, membership), then the validity of the questionnaire was established though a jury of (7) of the teaching staff of educational at Damascus and Tishreen Universities. Pilot sample consisted of (24) Kindergarten care takers, Reliability was established by Cronbach – Alpha Reliability at least (0.89). The research ended to the Availability Degree of Organizational Identification Dimensions of Kindergartens Care takers in Lattakia City was middle degree. There was no statistically significant differences in the availability degree of organizational identification Dimensions of Kindergartens Care takers in Lattakia according to (experience), while the results showed significant differences according to (educational qualification, training courses). The study recommended that promote healthy organizational climate in order to help the Kindergarten care takers to participate in the decision making process, which in return strengthens the concept of organizational identification for them. هدف البحث إلى تعرف درجة توافر التماثل التنظيمي لدى مربيات رياض الأطفال من وجهة نظرهن في مدينة اللاذقية، وتعرّف الفروق في متوسطات درجاتهن تبعاً للمتغيرات الآتية (عدد سنوات الخبرة، المؤهل العلمي والتربوي، الدورات التدريبية)، واشتملت عينة البحث على (198) مربية روضة للعام الدراسي 2018/2019، وتم استخدام المنهج الوصفي. ولتحقيق هدف البحث تم تصميم استبانة تضمنت (36) عبارة، ضمت ثلاثة أبعاد هي (الولاء التنظيمي، التشابه التنظيمي، العضوية)، وتم التأكد من صدقها من خلال عرضها على مجموعة مؤلفة من (7) محكمين مختصين في كليتي التربية بجامعتي دمشق وتشرين، و التأكد من ثباتها بتطبيقها على عينة استطلاعية شملت (24) مربية روضة و حساب معامل ألفا كرونباخ، والذي بلغ (0.89). وانتهى البحث إلى أن درجة توافر التماثل التنظيمي لدى مربيات الرياض في مدينة اللاذقية جاءت بدرجة متوسطة، كما بينت النتائج عدم وجود فروق ذات دلالة إحصائية بين إجابات المربيات تبعاً لمتغير عدد سنوات الخبرة، ووجود فرق ذو دلالة إحصائية تبعاً لمتغير المؤهل العلمي والتربوي لصالح حملة دبلوم التأهيل التربوي، وتبعاً لمتغير الدورات التدريبية لصالح المربيات اللواتي خضعن لدورات تدريبية. ومن خلال النتائج تم التوصل إليها قدمت مقترحات من أهمها: توفير مناخ تنظيمي ملائم لمساعدة مربيات الرياض بالمشاركة الفاعلة في عملية اتخاذ القرارات، من أجل تقوية مفهوم التماثل التنظيمي لديهم.